Medial minimally invasive helical plate osteosynthesis of the distal femur – a new technique. (September 2021) - Hohenberger, G.M.; Schwarz, A.M.; Grechenig, P.; Clement, B.; Staresinic, Mario; Bakota, Bore
Highlights: The results of this study indicate MIPO of the distal femur with a helical plate from a medial approach as a safe technique. In our sample, none of the included specimens showed any lesions of adjacent characteristics. The osteoarticular branch of the descending genicular artery needs to be dissected and preserved during performance of the approach and plate application . Abstract: Introduction: The goal of this study was to evaluate distal femoral minimally invasive plate osteosynthesis (MIPO) from a distal medial approach by use of a pre-bent helical implant. Material & Methods: A total of 18 lower extremities was evaluated. A 29.6 cm steel plate was constructed and pre-bent on bone specimens with a torsion of 55.7° A 5 cm incision was performed from the tip of the medial epicondyle alongside its centre in a proximal direction. The medial border of the vastus medialis was retracted anteriorly. The level of the proximal skin incision was determined using the length of the pre-bent plates. The proximal incision was performed at a length of 4 cm at the described height at a line between the lateral epicondyle and the tip of the greater trochanter. A raspatory was advanced beneath the vastus medialis in a proximal direction to create an extraperiosteal tunnel for plate insertion. The plate was fixed to the bone at its proximal and distal portion via screws. Following dissection, the distance between the nearest perforator to the proximal plate end was evaluated. The vertical distances between the medial border of the plate and the femoral artery and femoral nerve were measured at the level of the proximal plate end and at the level of the proximal margin of the vastoadductor membrane. Results: The most proximal perforating artery was located at a mean distance of 20.15 mm starting from the proximal plate margin. The mean interval between the medial border of the plate at the level of its proximal tip and the femoral artery was 51.9 mm. The average distance between the femoral nerve and the medial border of the proximal part of the plate was 42.3 mm. Regarding the interval between the medial border of the plate and the femoral artery, this was at a mean of 40.5 mm at the level of the proximal margin of the vastoadductor membrane. During dissection, none of the specimens showed any lesions of the adjacent anatomical characteristics. Conclusion: Our results indicate MIPO of the distal femur from a medial approach as a safe technique.